125Iodine brachytherapy via a trans‐superior vena cava approach in patients with metastases in middle mediastinal lymph nodes: a novel approach. Issue 3 (29th September 2016) - Liu, Bin; Li, Yuliang; Wang, Yongzheng; Wang, Wujie; Wang, Lili; Hertzanu, Yancu; Wang, Junjie; Zhang, Fujun
Abstract: Aim: Certain metastasis‐containing middle mediastinal lymph nodes cannot be approached by standard CT‐guided brachytherapy. We here describe a novel trans‐superior vena cava approach for such nodes. The aim of this prospective study was to assess the safety and clinical value of 125 iodine (I) brachytherapy via a trans‐superior vena cava approach in patients with metastases in middle mediastinal lymph nodes. Methods: From February 2008 to October 2011, 32 patients with 43 pathologically confirmed metastasis‐containing mediastinal middle lymph nodes underwent CT‐guided percutaneous 125 I brachytherapy via a trans‐superior vena cava approach. Their complications and treatment responses were analyzed. Variations in blood pressure, heart rate, hemoglobin concentration and oxyhemoglobin saturation before, during and after the procedure were recorded, as were complications, including hemorrhage, pneumothorax and development of Breuer's reflex. Treatment response was assessed according to the response evaluation criteria for solid tumors Version 1.1. Results: According to follow‐up CT examination after 6 months, 22 patients (68.75%) achieved complete responses and four (12. 5%) partial responses. One patient died of myocardial infarction. Overall response rate was 81.25%, with a local control rate of 87.5%. The median survival was 25.7 months, with progression‐free survival of 19.74 ± 0.81 months. The 1‐year and 3‐year overall survival rates were 53.13% and 28.13%. There were minimal immediate or delayed complications; no complications were severe. Conclusion: We consider this novel approach a safe means of treating certain mediastinal middle lymph node metastases.